2009
DOI: 10.1255/ejms.953
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Reaction Mechanisms for the Competitive Losses of H2, CH4 and C2H4 from Protonated Methylbenzenes—Implications to the Methanol-to-Hydrocarbons (MTH) Process

Abstract: We report the unimolecular decomposition following collisional activation of protonated mono-, di- and trimethylbenzenes as a function of collision energy. The resulting energy-resolved mass spectra are then used for the quality control of high-level quantum chemical models of the respective potential energy surfaces. Distinction is made between direct dissociation products (CH(4) or H(2)) and indirect products (alkenes), since formation of the latter requires extensive rearrangement of the molecular skeleton.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 49 publications
1
29
0
4
Order By: Relevance
“…[49,[54][55][56] Dissociation of protonated ortho-and meta-xylenium ions was found to yield mostly CH 4 -loss with a smaller fraction of H 2 - loss, while that of the ethylbenzenium ions yields mostly loss of ethene [49] and this was found to be in agreement with the C 8 H 11 + potential energy surface. [49,[54][55][56] Dissociation of protonated ortho-and meta-xylenium ions was found to yield mostly CH 4 -loss with a smaller fraction of H 2 - loss, while that of the ethylbenzenium ions yields mostly loss of ethene [49] and this was found to be in agreement with the C 8 H 11 + potential energy surface.…”
Section: The M/z 107 Ionsupporting
confidence: 57%
See 1 more Smart Citation
“…[49,[54][55][56] Dissociation of protonated ortho-and meta-xylenium ions was found to yield mostly CH 4 -loss with a smaller fraction of H 2 - loss, while that of the ethylbenzenium ions yields mostly loss of ethene [49] and this was found to be in agreement with the C 8 H 11 + potential energy surface. [49,[54][55][56] Dissociation of protonated ortho-and meta-xylenium ions was found to yield mostly CH 4 -loss with a smaller fraction of H 2 - loss, while that of the ethylbenzenium ions yields mostly loss of ethene [49] and this was found to be in agreement with the C 8 H 11 + potential energy surface.…”
Section: The M/z 107 Ionsupporting
confidence: 57%
“…[33,45,[49][50][51] Our infrared spectroscopic assignment can best be compared with a mass spectrometric gas-phase titration study of C 7 H 9 + ions formed by electron ionization of two monoterpenes, a-pinene and limonene (two C 10 H 16 isomers of adamantane). [49,[54][55] We consider the various protonated forms of ethylbenzene, xylene, vinylcyclohexadiene and methylcycloheptatriene as possible structures for the C 8 H 11 + fragment. The observation that our m/z 93 spectrum best resembles the computed spectra of protonated toluene, while at the same time not excluding contributions of the dihydrotropylium ion is in good agreement with this study and also with the spectroscopically confirmed most favorable protonation sites being the ortho and para positions.…”
Section: The M/z 93 Ionmentioning
confidence: 99%
“…[69,70] Ebenso wurden Methylbenzole in den parallelen Untersuchungen von Haw und Mitarbeitern als die organischen Reaktionszentren der MTH-Katalyse an H-SAPO-34-Katalysatoren identifiziert, [71][72][73][74][75] was mit den Befunden von Arstad und Kolboe übereinstimmte. [87,88] Die Alternative zum Abschälmodell ist das von Mole und Mitarbeitern [61,62] vorgeschlagene und später von Haw et al verfeinerte [76,77] Seitenkettenmethylierungsmodell, das in Abbildung 10 (rechts) für die Propenbildung dargestellt ist. Dabei wurde die Reaktivität von verschiedenen Polymethylbenzolen und Butylbenzolisomeren untersucht.…”
Section: Vorarbeiten: Etappen Auf Dem Weg Zum Kohlenwasserstoffpool-munclassified
“…Der Hauptunterschied zwischen dem generellen Terminus "autokatalytischer Mechanismus" und dem "Kohlenwasserstoffpool-Mechanismus" scheint daher die Diffusionseinschränkung der Spezies im Kohlenwasserstoffpool zu sein. [87,88] Aus diesem Verständnis heraus scheint es begründet, dass der Kohlenwasserstoffpool-Mechanismus über H-ZSM-5, der auf den niederen Polymethylbenzolen basiert, hauptsächlich Ethen hervorbringt, während bei H-beta die hçheren Polymethylbenzole aktiv sind und somit Propen begünstigt ist. Somit scheint es praktischer, sich an die verallgemeinernde Definition des Terminus "Kohlenwasserstoffpool" zu halten, wie er von Dahl und Kolboe vorgeschlagen wurde, und damit sowohl Alkene als auch mehrfach methylierte Benzole/ Benzeniumionen einschließlich des Heptamethylbenzeniumkations als Endprodukt der Methylierung zu umfassen.…”
Section: Methanol-reformierungunclassified
See 1 more Smart Citation